Protective Encapsulation of a Bioactive Compound in Starch–Polyethylene Glycol-Modified Microparticles: Degradation Analysis with Enzymes - Chapa, Christian (2024)
Starch is a promising polymer for creating novel microparticulate systems with superior biocompatibility and controlled drug delivery capabilities. In this study, we synthesized polyethylene glycol (PEG)-modified starch microparticles and encapsulated folic acid using a solvent-mediated acid-base precipitation method with magnetic stirring, which is a simple and effective method. To evaluate particle degradation, we simulated physiological conditions by employing an enzymatic degradation approach. Our results with FTIR and SEM confirmed the successful synthesis of starch–PEG microparticles encapsulating folic acid. The average size of starch microparticles encapsulating folic acid was 4.97 μm and increased to 6.01 μm upon modification with PEG. The microparticles were first exposed to amylase at pH 6.7 and pepsin at pH 1.5 at different incubation times at physiological temperature with shaking. Post-degradation analysis revealed changes in particle size and morphology, indicating effective enzymatic degradation. FTIR spectroscopy was used to assess the chemical composition before and after degradation. The initial FTIR spectra displayed characteristic peaks of starch, PEG, and folic acid, which showed decreased intensities after enzymatic degradation, suggesting alterations in chemical composition. These findings demonstrate the ongoing development of starch–PEG microparticles for controlled drug delivery and other biomedical applications and provide the basis for further exploration of PEG–starch as a versatile biomaterial for encapsulating bioactive compounds.